HUBUNGAN KEKUATAN OTOT TUNGKAI DAN KOORDINASI MATA KAKI TERHADAP HASIL SHOOTING BOLA DIAM KE ARAH GAWANG - Manurung, Jack suman Rulis (Universitas Tanjungpura, 2019)
The purpose of this research is to find out: 1) The relationship of leg muscle strength to the results of shooting the silent ball towards the goal. 2) Relationship between ankle coordination and the result of shooting the ball silently towards the goal. 3) The relationship between leg muscle strength and ankle coordination towards the results of shooting the ball silently towards the goal.The method used in this study is a method of correlation with test and measurement techniques. Data analysis was carried out by a computerized system with simple or multiple regression analysis. The population in this study were students who participated in extra-curricular football at Pontianak's N 8 High School, totaling 22 people. In this study, there was no sampling technique because it took all the population who participated in 22 extra-curricular activities.The results of the analysis of the data obtained indicate that: 1) There is a relationship between leg muscle strength to the results of shooting the silent ball towards the goal. 2) There is a coordination relationship between the ankles and the result of shooting the silent ball towards the goal. 3) There is a relationship between leg muscle strength and ankle coordination towards the results of shooting the silent ball towards the goal.The amount of donation given by leg muscle strength to the results of silent ball shooting towards the goal was 52.1%, while the coordination contribution of the ankle to the results of silent ball shooting towards the goal was 25.3%. While the magnitude of the contribution given by the two variables, namely leg muscle strength and ankle coordination was 59% of the results of shooting the silent ball towards the goal. It is recommended that in addition to practicing silent ball shooting techniques towards the goal, leg muscle strength should be taken into consideration for the trainer in giving a portion of training.